Exchange rate fluctuations and the financial channel in emerging economies - Joscha Beckmann; Mariarosaria Comunale (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
This paper assesses the financial channel of exchange rate fluctuations for emerging countries and the link to the conventional trade channel. We analyze whether the effective exchange rate affects GDP growth, the domestic credit and the global liquidity measure as the credit in foreign currencies, and how global liquidity affects GDP growth. We make use of local projections in order to look at the shocks' transmission covering 11 emerging market countries for the period 2000Q1- 2016Q3. We find that foreign denominated credit plays an important macroeconomic role, operating through various transmission channels. The direction of effects depends on country characteristics and is also related to the policy stance among countries. We find that domestic appreciations increase demand regarding foreign credit, implying positive effects on investment and GDP growth. However, this is valid only in the short-run; in the medium-long run, an increase of credit denominated in foreign currency (for instance, due to appreciation) decreases GDP. The financial channel works mostly in the short run except for Brazil, Malaysia, and Mexico, where the trade channel always dominates. Possibly there is a substitution effect between domestic and foreign credit in the case of shocks in exchange rates.
URN:NBN:fi:bof-202108301411
Keywords: F31; F41; F43; G15; 330; emerging markets; financial channel; exchange rates; global liquidity